Infantile Bullous Pemphigoid: A Case Report - Bin Rubaian NF; Alakloby OM; Alhuraish DS; Alzoabi N; Alqahtani J; AlAkloby SO; AlJindan FA (Dove Medical Press, 2024)
Nouf F Bin Rubaian,1 Omar Mohammed Alakloby,1 Deemah S Alhuraish,2 Nasser Alzoabi,1 Jamal Alqahtani,1 Sara Omar AlAkloby,1 Fatma A AlJindan3 1Dermatology Department, Imam Abdulrahman Bin Faisal University, King Fahad Hospital of the University, Khobar, Saudi Arabia; 2College of Medicine, Imam Abdulrahman Bin Faisal University, Khobar, Saudi Arabia; 3Pathology Department, Imam Abdulrahman Bin Faisal University, King Fahad University Hospital, Khobar, Saudi ArabiaCorrespondence: Deemah S Alhuraish, Email Deemahalhuraish@gmail.comBackground: Infantile bullous pemphigoid (IBP) is an exceptionally rare acquired autoimmune subepidermal bullous disorder characterized by vesicles, bullae, and additional manifestations, such as urticarial and infiltrated papules, plaques, or eczematous lesions. These skin lesions can lead to eroded and crusted regions after healing, and in some cases, rapid blister rupturing causes extensively eroded areas. Reporting these rare cases is crucial to improving our understanding, diagnosis, and treatment of IBP.Case Presentation: In this report, we present the clinical case of a 4-month-old male infant with generalized tense bullae causing irritability and sleeplessness. This case highlights the distinctive clinical features of IBP, including the development of multiple generalized tense bullae over 2 weeks. The pathological examination findings confirmed the diagnosis of IBP.Conclusion: This case emphasizes the significance of early identification and proper management of IBP. Our thorough assessment, which incorporates pathological verification and therapeutic interventions, has advanced our understanding of IBP. Additionally, this case underscores the vital need for timely diagnosis and personalized treatment approaches for affected infants.Keywords: direct immunofluorescence, immunoglobulin G, complement factor C3, blistering skin lesions, Infant, Pemphigoid